Study of wear and durability of gear cuttering tools - Tattimbek Гулерке; Sherov Карибек; Ainabekova Сауле; Imanbaev Ернат; Tussupbekova Гулим (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
This article presents research findings on the wear of gear cutting tools. The purpose of the scientific research is to identify the causes of wear of gear cutting tools, as well as to develop a method for processing the cavities of gear teeth and the design of a special tool for its implementation. A review of scientific works on the study of wear of gear cutting tools has been carried out and factors influencing the intensity of wear have been identified. It was revealed that one of the main factors influencing the wear of a gear cutting tool is the module of the gear being processed and as it increases, the wear of the tool increases accordingly. This is especially the case in the manufacture of large-module cylindrical gears, in particular in the process of machining tooth cavities. At which the intensity of tool wear increases, the accuracy and productivity of processing decreases, and the cost of the operation increases. This state of the process is primarily due to the need to remove a large volume of metal from the cavities of the gear wheel. To solve this problem, a new resource-saving method of thermal friction processing of tooth cavities of large-module cylindrical gears is proposed. Designs of modular friction disk mills have been developed for processing the tooth cavities of cylindrical gears using thermal friction milling and thermal friction milling with pulse cooling. Prototypes of a smooth modular friction disk mill and special equipment for mounting it on a screw-cutting lathe were manufactured.